1988
DOI: 10.1007/bf00378476
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and muscle endurance of middle-aged women and men associated to type, duration and intensity of muscular load at work

Abstract: Muscle strength and muscle endurance in groups with different occupational muscular load was studied among 60 women and 69 men. The mean age of the subjects was 52.0 +/- 3.4 years. Isometric grip and trunk strength were measured on dynamometers, and dynamic muscle endurance by sit-ups. A job analysis was done with the AET method including the assessment of intensity, duration and type of muscular work of each subject. According to the job analysis, the subjects were classified into groups with low or high musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Furthermore, most of the ''cases'' were also found to have low muscle endurance (which correlates to aerobic capacity), as well as poor balance and coordination. Earlier studies have shown a negative relationship between capacity (both aerobic and muscular strength) and long-lasting physical activity at work (Nyga˚rd et al 1987(Nyga˚rd et al , 1988Era 1992;Torge´n et al 1999). Females in the highest quartile of TWA-MET work had, however, lower muscle endurance in their abdomen and legs and worse coordination than subjects in the lowest quartile of TWA-MET work .…”
Section: Physical Demands and Physical Capacitymentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, most of the ''cases'' were also found to have low muscle endurance (which correlates to aerobic capacity), as well as poor balance and coordination. Earlier studies have shown a negative relationship between capacity (both aerobic and muscular strength) and long-lasting physical activity at work (Nyga˚rd et al 1987(Nyga˚rd et al , 1988Era 1992;Torge´n et al 1999). Females in the highest quartile of TWA-MET work had, however, lower muscle endurance in their abdomen and legs and worse coordination than subjects in the lowest quartile of TWA-MET work .…”
Section: Physical Demands and Physical Capacitymentioning
confidence: 90%
“…A positive relationship between physical capacity and physical workload among young workers has been documented (Schibye et al 2001). In studies among middle-aged and elderly workers who have had physically strenuous jobs during their careers, a negative relationship between capacity and physical activities at work has been observed (Nyga˚rd et al 1987(Nyga˚rd et al , 1988Era 1992;Miettinen and Louhevaara 1994). In contrast to these findings, other studies find a positive relationship between muscle strength and workload among elderly workers (e.g.…”
Section: Introductionmentioning
confidence: 87%
“…The influence of work-related exposures on muscle strength has been discussed since the 1980s, where occuhas been discussed since the 1980s, where occupational physical activity was thought to strengthen manual workers (1). Since then the focus has been on the deteriorating effects of physical exposures, which are now known to be important risk factors in the development of musculoskeletal symptoms and diseases (2,3).…”
mentioning
confidence: 99%
“…A positive relationship between physical aerobic capacity and physical workload has been documented for young workers (20). In studies among middle-aged and elderly workers who have had physically strenuous jobs during their careers, a negative relationship has been observed between aerobic capacity and physical activities at work (21)(22)(23)(24). In contrast to these findings, other studies have found a positive relationship between muscle strength and workload among elderly workers (20).…”
mentioning
confidence: 98%